Congenital nasolacrimal duct obstruction in Kayseri, Turkey - Ekinciler, Ömer Faruk; Doğan, Hakkı; Tatlışen, Nursen; Karaküçük, Sarper (The Turkish Journal of Pediatrics, 1994)
Congenital nasolacrimal duct obstruction was diagnosed in 170 patients between 1982 and 1991 in Kayseri, Turkey, and 111 patients were treated with massage plus topical antibiotics (MBC), pressure irrigation (PI), probing (PRB) or infracturing of the inferior turbinate (INF). The ages of the patients ranged from one week to 15 years. The obstruction was bilateral in 38 patients.Among the 149 obstructed lacrimal drainage systems of 111 patients, 101 were cleared by MBC (67.8%), 30 by PI (20.1%), eight by PRB (5.3%) and two by INF (1.3%). Eight cases were unsuccessful (5.3%), and the overall success rate was 94.6%.The efficacy of four interventions was correlated to the patients’ ages and to the presenting pathology. MBC carried out at the serofibrinous stage and at 7-13 months was more effective than other interventions, with a statistical significance (p < 0.01).The effectiveness of four interventions is discussed, with an emphasis on the importance of early MBC. The importance of fluoroscopy during PI or PRB is also emphasized.
Keywords: nasolacrimal duct; neonatal dacryocytitis; pressure irrigation; probing; fluoroscopy